Moscas ectoparasitas (Diptera, Hippoboscoidea, Nycteribiidae) de morcegos (Mammalia, Chiroptera) do Estado do Paraná, Brasil. I. Basilia, taxonomia e chave pictórica para as espécies - Graciolli, Gustavo (2001)
A survey of nicteribiid batflies (Diptera: Nycteribiidae) was done in Paraná State, Brazil. Seven species of Basilia Miranda Ribeiro, 1903 were recorded. Basilia ortizi Machado-Allison, 1963 is a new record for Brazil.. Two species are new records for Paraná State, Basilia carteri Scott, 1936 and Basilia juquiensis Guimarães, 1946. The male of B. juquiensis Guimarães is characterized. Basilia lindolphoi sp. n. is described. Pictorial keys to species are presented, and female abdomens are illustrated.